Natural and enhanced carbonation of lime in its different applications: a review - Campo F. P.; Tua C.; Biganzoli L.; Pantini S.; Grosso M. (Environmental Technology Reviews, 2021)
Lime is a product derived from the thermal decomposition of limestone (mainly calcium carbonate, CaCO3) into quicklime (CaO) and carbon dioxide (CO2), also called calcination. Controlled reaction with water is used to manufacture hydrated lime (Ca(OH)2) products. Lime is used in a wide variety of applications: metals industry, construction materials sector, civil engineering, environmental protection, agriculture, and chemical industry. Lime production is one of the sources of anthropogenic CO2 emissions resulting in global warming and ocean acidification. However, a proportion of the CO2 emitted during the calcination is reabsorbed by the lime during the product life within its different applications. This process called carbonation is thermodynamically favoured because it is exothermal. It allows permanent CO2 storage in a stable product since the lime combines with gaseous CO2 reforming CaCO3. This paper reports a comprehensive literature review on the carbonation potential of lime in different applications. The total carbonation potential is assessed as carbonation rate, i.e. the ratio between the CO2 reabsorbed through carbonation during the operational life of lime and the CO2 emitted during limestone calcination. This study provided preliminary evidence that, based on the current EU market, on average 23–33% of lime process emissions are carbonated during the use phase. Carbonation over time is also analysed for the lime applications where information is available. For three applications, namely water, flue gas cleaning and pulp and paper, the carbonation reaction is instantaneous. Up to 22% of the calcination emissions are absorbed within five years based on the current EU market.